Association Between BMI and Incidence of Inguinal Hernia in Adult Males (Medical Forum Monthly, 2024)
Objective: To assess association between incidence of inguinal hernia and body mass index in adult males.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the Surgery Department of Central Park Teaching Hospital, Lahore from June 2023 to January 2024.Methods: Non-probability sampling technique was employed and a total of 80 patients were recruited and patients having bilateral inguinal hernia, strangulated hernia and femoral hernia were excluded. Categorical variables were assessed and frequencies and percentages were calculated. Fisher Exact test was employed for the comparison of incidence of hernia in study groups.Results: A total 80 patients having unilateral inguinal hernia were recruited for the study with the mean age of 28.15 + 13.65 years. Assessment of incidence of hernia and BMI was made, it was observed that 72.5% of the patients (n=58) had right sided inguinal hernia (RIH) while 27.5% of the patients (n=22) had left sided inguinal hernia. It was noted that those patients who had RIH, only 31.38% of the patients had BMI greater than 23.5 kg/m2 while other patients had BMI lower than cut-off value.Conclusion: A preventative association of increased BMI with hernia development that needs future more detailed evaluation. A better understanding of these dynamics could element enhancement of risk profile identification and preventive measures in surgical work.